The Palatability Level of the Application of Animal Welfare Aspects in Laboratory Animal Management at the Animal Lab of Hasanuddin University Veterinary Teaching Hospital - AMRIANI, RINI; A. MUH. ICHLASUL AKMAL; MUHAMMAD DIRGA GIFARDI; DIDIK IMAM SAKIRIN; DWI KESUMA SARI; A. MAGFIRA SATYA APADA (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2025)
According to Law Number 18 of 2009, animal welfare encompasses all aspects related to the physical and mental condition of animals based on their natural behaviors. Animal welfare includes how the management of laboratory animal housing is evaluated in terms of cage conditions, environment, and nutritional fulfillment. The objective of this study is to examine the correlation between the application of animal welfare aspects, including housing management, environment, and nutrition, on the palatability levels of laboratory animals. The research method involved dividing the treatment groups into eight groups, with each group consisting of three rats, for a total of 24 rats. The rat groups were categorized based on housing management, which was assessed based on cage size and body weight, sterilized versus non-sterilized bedding, optimum versus non-optimum temperature and humidity, and the frequency of feeding once a day or twice a day. The results showed that groups one and two exhibited higher average palatability levels compared to the other groups (17.5 and 16.5 grams, respectively), while groups four and five exhibited the lowest palatability levels (10.5 and 11.5 grams). Normality tests indicated that the data were normally distributed (P>0.05), and homogeneity tests showed that the data from the different groups were consistent (homogeneous) (P>0.05). Based on the normality and homogeneity tests, statistical analysis (ANOVA) was conducted. The ANOVA results indicated a significant effect (P